Absorption studies in patients six to 10 years after construction of ileostomy reservoirs. Issue 6 (June 1979) - Nilsson, L O; Andersson, H; Hultén, L; Jagenburg, R; Kock, N G; Myrvold, H E; Philipson, B
Abstract : The absorption of fat, bile salts, and vitamin B12 was studied in 14 proctocolectomised patients six to 10 years after construction of a continent ileostomy. All patients were in excellent health and displayed no signs of malnutrition. Schilling test disclosed subnormal absorption of vitamin B12 in one patient and borderline values in five. Faecal loss of bile acid was increased in 12 patients and fat malabsorption occurred in two. Except for slightly pathological liver tests in two patients, routine laboratory tests, including plasma concentration of vitamin B12 and folic acid, were normal. There were no signs of sodium or potassium depletion.